Mechanistic insights into the gold chemistry of allenes - Yang, Weibo; Hashmi, A. Stephen K. (Chemical Society reviews, 2014)
Although most mechanistic studies on gold-catalysed reactions focused on alkynes as substrates, some knowledge about gold-catalysed conversions of allenic substrates has been obtained. This contribution summarises these insights into the reaction mechanisms of gold-catalysed transformations of allenes which are based on computational studies, labelling studies, the detection of intermediates, chirality transfer and diastereoselective product formation.
Gesehen am 09.10.2020